Análisis de funciones del trabajador social en el campo educativo - Cívicos Juárez, Asunción; González González, Angeles; Pérez González, Beatriz; Hernández Hernández, Manuel (Acciones e Investigaciones Sociales, 2011)
Análisis de funciones del trabajador social en el campo educativo